Pemberdayaan Seni Kubro Siswo Untuk Pelestarian Budaya Lokal di Desa Masda Makmur - Rohmah, Rina Ari; Dona, Dona; Lesmana, Andi (Penerbit Widina, Widina Media Utama, 2024)
The preservation of local culture in Masda Makmur Village, Rokan Hulu Regency is the main challenge during the lack of participation of the younger generation in the traditional art of Kubro Siswo. The Kubro Siswo Arts Group has difficulties in maintaining the regeneration of members and faces limited support facilities and promotions. This service program aims to preserve the culture of Kubro Siswo through increasing managerial capacity and cultural arts skills, especially for the younger generation. The methods used in this program include socialization, management and marketing training, website and social media development, and the provision of souvenir production equipment in the form of t-shirt screen printing. The results of the program show an increase in the interest of the younger generation in local arts, the implementation of cultural arts festivals, and the increase in group capacity in the management of cultural arts organizations and promotions. In addition, diversification efforts through the production of screen-printing t-shirts have a positive impact in supporting the economic independence of the group. In conclusion, this program has succeeded in increasing public awareness of the importance of preserving local culture and providing sustainable solutions to maintain the existence of Kubro Siswo art during modernizationABSTRAKPelestarian budaya lokal di Desa Masda Makmur Kabupaten Rokan Hulu menjadi tantangan utama di tengah minimnya partisipasi generasi muda dalam kesenian tradisional Kubro Siswo. Kelompok Kesenian Kubro Siswo mengalami kesulitan dalam menjaga regenerasi anggota serta menghadapi keterbatasan dukungan fasilitas dan promosi. Program pengabdian ini bertujuan untuk melestarikan budaya Kubro Siswo melalui peningkatan kapasitas manajerial dan keterampilan seni budaya, khususnya bagi generasi muda. Metode yang digunakan dalam program ini meliputi sosialisasi, pelatihan manajemen dan pemasaran, pengembangan website dan media sosial, serta penyediaan peralatan produksi cinderamata berupa sablon kaos. Hasil program menunjukkan peningkatan minat generasi muda terhadap kesenian lokal, terselenggaranya festival seni budaya, serta peningkatan kapasitas kelompok dalam pengelolaan organisasi dan promosi seni budaya. Selain itu, usaha diversifikasi melalui produksi kaos sablon memberikan dampak positif dalam mendukung kemandirian ekonomi kelompok. Kesimpulannya, program ini berhasil meningkatkan kesadaran masyarakat terhadap pentingnya pelestarian budaya lokal dan memberikan solusi berkelanjutan untuk menjaga eksistensi kesenian Kubro Siswo di tengah modernisasi.